Direct Plasma Potential Measurements by Ball‐Pen Probe and Self‐Emitting Langmuir Probe on COMPASS and ASDEX Upgrade. Issue 3 (April 2014) - Adamek, J.; Horacek, J.; Seidl, J.; Müller, H. W.; Schrittwieser, R.; Mehlmann, F.; Vondracek, P.; Ptak, S.; COMPASS Team,; ASDEX Upgrade Team,
Abstract Experimental investigations of the plasma potential by means of a ball‐pen probe and self‐emitting Langmuir probe technique were performed on the tokamaks COMPASS and ASDEX Upgrade. A spontaneous transition between the cold and self‐emitting Langmuir probe has been observed during the deep reciprocation in the vicinity or even inside the last closed flux surface (LCFS) of both tokamaks. These measurements of the plasma potential allow us to compare two independent probe techniques based on heating and non‐heating processes. The observed different conditions of the spontaneous transition can be ascribed to different physical mechanisms. Nevertheless, the comparison of the power spectra of ball‐pen probe and self‐emitting Langmuir probe indicates very good agreement in all measurements and therefore these two probe techniques are interchangeable. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)